Organizational Structure Around Web-Scale Discovery Services in Canadian Academic Libraries - Wong, Sandra (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
This study analyzed how Canadian post-secondary libraries manage and administer their web-scale discovery service. Through a combination of survey responses and semi-structured interviews, the author investigated how Canadian academic libraries support their web-scale discovery service from an organizational structure perspective. Academic libraries can manage their discovery service from a technical services unit, a library systems or a web services department, or by a committee. However, there is consensus that a discovery service requires collaboration among many functional areas. Discovery service leaders often have organizational awareness to break down the silos between traditional library functions to perform the various duties related to managing and administering their web-scale discovery service. Individuals responsible for their discovery service work collaboratively with staff in many different areas and often have a strong user-centred focus.